Spatial patterns of microparticle ingestion by myctophids near a major river mouth in the northeast Pacific Ocean - Boisen, Olivia C.; Brodeur, Richard D.; Brander, Susanne M.; Heppell, Scott A. (Frontiers in Marine Science, 2024)
Introduction Plastics carried in the outflow of major rivers can be made available and subsequently ingested by marine fishes, causing lethal and sublethal effects. Highly abundant, vertically migrating myctophids play a crucial role in facilitating nutrient cycling between the epi- and mesopelagic zones. However, this diel movement may also make myctophids significant conduits for transporting ingested microparticles from surface waters to deeper food webs. Methods We examined the gastrointestinal tracts of 340 myctophids caught at varying distances from the Columbia River mouth in the epipelagic zone of the northeast Pacific Ocean to determine if proximity to a presumed point source influences microparticle ingestion. Results While we found no direct spatial connection with ingestion frequency, we discovered that (a) 34% of myctophids had either synthetic or other anthropogenic particles retained in their GI tract, (b) microparticle ingestion was higher in an active-feeding species of myctophid (Tarletonbeania crenularis) than an inactive-feeding species (Stenobrachius leucopsarus), and (c) species and standard length were the most influential predictors of microparticle consumption in our best fit model. Discussion Our failure to detect a significant relationship between distance from a source and ingestion by myctophids is likely due to the particles undergoing fluctuations in dispersal patterns once they enter the ocean, particularly for microfibers which can be transported across large distances. Biological factors like body size may be more relevant to understanding microparticle ingestion patterns in mesopelagic fishes. Overall, our study highlights the potential role myctophids serve as multidirectional transporters of microparticles in Northern California Current food webs, with potential impacts on fisheries and human food systems.